Associations Between Antibody Fc-Mediated Effector Functions and Long-Term Sequelae in Ebola Virus Survivors - Paquin-Proulx, Dominic; Gunn, Bronwyn M.; Alrubayyi, Aljawharah; Clark, Danielle V.; Creegan, Matthew; Kim, Dohoon; Kibuuka, Hannah; Millard, Monica; Wakabi, Salim; Eller, Leigh Anne; Michael, Nelson L.; Schoepp, Randal J.; et al. (Frontiers in Immunology, 2021)
Antibodies that mediate non-neutralizing functions play an important role in the immune response to Ebola virus (EBOV) and are thought to impact disease outcome. EBOV has also been associated with long term sequelae in survivors, however, the extent to which antibodies that mediate non-neutralizing functions are associated with the development of these sequelae is unknown. Here, the presence of antibodies mediating different effector functions and how they relate to long-term sequelae two years after the 2007 Bundibugyo Ebola virus (BDBV) outbreak was investigated. The majority of survivors demonstrated robust antibody effector functional activity and demonstrated persistent polyfunctional antibody profiles to the EBOV glycoprotein (GP) two years after infection. These functions were strongly associated with the levels of GP-specific IgG1. The odds of developing hearing loss, one of the more common sequelae to BDBV was reduced when antibodies mediating ADCP, ADCD, or activating NK cells were observed. In addition, hearing loss was associated with increased levels of several pro-inflammatory cytokines and levels of these pro-inflammatory cytokines were associated with lower ADCP. These results are indicating that a skewed antibody profile and persistent inflammation may contribute to long term outcome in survivors of BDBV infection.